Comment on "Carbon in Trees in Tasmanian State Forest". (29th June 2011) - Dean, Christopher
Abstract : Moroni et al. (2010) reported extant, spatially representative carbon stocks for Tasmania's State forest. Their disputation of earlier work, contextual setting, redefinition of carbon carrying capacity (CCC), methods, adoption of ecological concepts and consequent conclusions on carbon flux were investigated. Their reported data was very useful; however, the absence of sufficient context and fundamental equations was atypical of scientific publications; old-growth should have been differentiated from mature forests and wet-sclerophyll from mixed-forest, redefinition of CCC was unwarranted, and several of their arguments and conclusions appeared unwarranted. From their graphs and tables, I estimated that the carbon deficit in State forest biomass (the amount below CCC) due to commercial forestry was conservatively 29(±4) Tg (or 106(±13) Mtonnes CO2 -eq; with couped-production forests 29(±6)% below CCC) a greenhouse gas mitigation opportunity—indicating the usefulness of the existing definition of CCC. Also, using their data, earlier work on long-term fluxes accompanying conversion of wet-eucalypt forests to harvesting cycles was found to correspond to 0.56(±0.01) Mha (i.e., >1/3 of State forest), 76(±2)% of which is in the commercial production area—in contrast to their claim that earlier work referred to a small and atypical proportion.